Expression of zinc finger transcription factors (ZNF143 and ZNF281) in serous borderline ovarian tumors and low-grade ovarian cancers - Paweł Sadłecki; Marek Grabiec; Dariusz Grzanka; Jakub Jóźwicki; Paulina Antosik; Małgorzata Walentowicz-Sadłecka (BMC, 2019)
Abstract Low-grade ovarian cancers represent up to 8% of all epithelial ovarian carcinomas (EOCs). Recent studies demonstrated that epithelial-mesenchymal transition (EMT) is crucial for the progression of EOCs. EMT plays a key role in cancer invasion, metastasis formation and chemotherapy resistance. An array of novel EMT transcription factors from the zinc finger protein family have been described recently, among them zinc finger protein 143 (ZNF143) and zinc finger protein 281 (ZNF281). The study included tissue specimens from 42 patients. Based on histopathological examination of surgical specimens, eight lesions were classified as serous borderline ovarian tumors (sBOTs) and 34 as low-grade EOCs. The proportions of the ovarian tumors that tested positively for ZNF143 and ZNF281 were 90 and 57%, respectively. No statistically significant differences were found in the expressions of ZNF143 and ZNF281 transcription factors in SBOTs and low-grade EOCs. Considering the expression patterns for ZNF143 and ZNF281 identified in this study, both sBOTs and low-grade EOCs might undergo a dynamic epithelial-mesenchymal interconversion. The lack of statistically significant differences in the expressions of the zinc finger proteins in sBOTs and low-grade serous EOCs might constitute an evidence for common origin of these two tumor types.